Optimizing Neutronic and Photonic Performance in Irradiation Systems of Symmetric TRIGA Cores - S. M. Shauddin (Atom Indonesia, 2023)
The BAEC TRIGA MARK-II Research Reactor (BTRR) in Bangladesh has been used for a wide range of purposes, including basic and applied nuclear research and human resource development. Therefore, its core management should be flexible to meet various objectives with different priorities and to deliver the best possible outcome. In this study, neutron and gamma photon flux variation was studied at different radial and axial irradiation systems of the current core (C-0) as well as six symmetric reconfigurations (C-1, C-2, C-3, C-4, C-5, and C-6) of the existing BTRR using the universal MCNP code. While keeping the exact core component and material density, the symmetric reconfigured cores were modeled based on core criticality calculation and excess reactivity in the critical state. Finally, it was observed that the reconfigured core C-1 has the best neutronic and photonic performance at the irradiation systems compared to other reconfigured cores, against the reference core C-0.